Genotypic and Phenotypic Comparison of Enteroaggregative Escherichia coli Isolates from HIV-Positive and Non-HIV Diarrheal Samples - Jafari, Anis; Shafaei, Ebrahim; Oloomi, Mana; Aghasadeghi, Mohammad-Reza; Bouzari, Saeid (Current HIV Research, 2013)
Enteroaggregative Escherichia coli (EAEC) have been isolated from both HIV-positive and non-HIV diarrheal samples. In this study a collection of 18 isolates from these two groups were compared for biofilm formation and antibiotic resistance and for the presence of 14 virulence-related genes. All the HIV-positive and over 66% of the non- HIV strains were PCR-negative for adhesion-related sequences indicating that as yet unknown adhesins may play a role. However, despite some variations, the prevalence rate of the virulence-related genes was not significantly different in the two groups. HIV-positive isolates were biofilm producer but only a single weak biofilm former was observed among the non-HIV strains. The rate of resistance to most of the antibiotics used was higher among the HIV-positive group than the non-HIV isolates, but was significantly higher for amoxicillin-calvulanic acid (100%) and nalidixic acid (55.5%). Pulse field gel electrophoresis of the isolates produced 17 unique profiles reflecting the exiting heterogeneity of the isolates.
Keywords: HIV-positive diarrhea